Seasonal variation in efficacy of anthelmintics and prevalence of anthelmintic resistance in gastrointestinal nematodes of sheep in Rajasthan - SWARNKAR, C P; SINGH, D (The Indian Journal of Animal Sciences, 2012)
The objective of the study was to ascertain the extent of variation in the efficacy of anthelmintics in different seasons and its correlation with status of anthelmintic resistance in gastrointestinal nematodes of sheep in different agroclimatic regions of Rajasthan. Sheep flocks (141) distributed in different agroclimatic conditions were used for study. The efficacy of anthelmintics was determined by faecal egg count reduction test (FECRT). The seasonal analysis of data on % FECR exhibited that overall efficacy ranged from 56.80±3.99 (June-August) to 79.76±2.23 (December – February) and from 72.65±6.83 (March – May) to 91.46±2.07 (December – February) for benzimidazole and tetramisole, respectively. No seasonal variation was observed for efficacy of closantel against Heamonchous contortus in sheep and it remained > 99%. The anthelmintic treatment during climatic extreme (winter) when there is little or no translation of exogenous stage was found responsible for increased frequency of flocks possessing benzimidazole-resistant worms. The trend analysis exhibited positive skewness with platykurtic curve for benzimidazole while for tetramisole the skewness is moderately negative with leptokurtic curve. Our findings are suggestive that there is need for regular monitoring of drug efficacy and anthelmintic resistance, formulation of epidemiology based integrated worm management programme and in-depth study on role of refugia on drug efficacy.